PENGEMBANGAN DESAIN PEMBELAJARAN JARAK JAUH PENYULUH PERPAJAKAN DALAM PEMBELAJARAN NORMAL BARU - Aniek Juliarini; Taufik Kurachman (Puslatbang KHAN, 2020)
Preparation of Taxation Counselors Officials must be implemented during this new normal period. Material for taxation counselors consists of many components which need further development in order for distance learning to be successful. Research for the development of this learning design was carried out at the implementation stage. The research was conducted using quantitative and qualitative/descriptive methodology. The target of the research was Distance Learning for Taxation Counselors at the Cimahi Financial Education and Training Center, held on 24-28 August 2020. The data analyzed was primary data in the form of a questionnaire produced using the Google Forms platform, data on theoretical and practical exam results, and observation data. The research data was processed, presented graphically, and analyzed descriptively. The key findings of this study suggest that Distance Learning for Taxation Counselors at the Cimahi Financial Education and Training Center ran effectively, the learning remained active and interesting, and the test results of most participants are very good. However, almost of all participants prefer classical learning